The application of a conceptual framework to integrate oral health in childhood cancer care - Anupama Ivaturi, MDS; Rachna Seth; Harsh Priya, MDS (Elsevier, 2021)
Childhood cancer is a disease which is increasing in number. The good part is that if intervened early it can be treated with good prognosis. However, it is the utmost requirement of the medical fraternity to ease the quality of life of the paediatric patient in this journey. Oro-dental health and good oral health related quality of life is also deemed necessary for these childhood disease warriors. The provision of an inclusive facility of oral health care along with the paediatric cancer treatment has been emphasized. Utilization of services of preventive dentistry ranging from knowledge reinforcement of oral hygiene to awareness and treatment of early and late oral complications during the course of chemo-and radiotherapy is the ideal oral health care delivery approach in this population. The basic idea is to present an conceptual framework to integrate oral health into the childhood cancer care in an all embracing manner.